CADANGAN PROSPEKTIF ASURANSI JIWA BERJANGKA DENGAN HUKUM DE MOIVRE - Dini Ramadani; Johannes Kho; Aziskhan ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article  discusses the calculation of the prospective reserve for term life insurance with  De Moivre’s  law  to someone  with the age of  x  where the money  will  be paid  only if the insurance client  dies within the term of protection.  Based on the calculation, this prospective reserve is influenced by  single premium,  present value of annuity due,  and annual premium, for which the calculation is done using De Moivre’s law.